Dopant titrating ion mobility spectrometry for trace exhaled nitric oxide detection. (5th January 2015) - Peng, Liying; Hua, Lei; Li, Enyou; Wang, Weiguo; Zhou, Qinghua; Wang, Xin; Wang, Changsong; Li, Jinghua; Li, Haiyang
Abstract: Ion mobility spectrometry (IMS) is a promising non-invasive tool for the analysis of exhaled gas and exhaled nitric oxide (NO), a biomarker for diagnosis of respiratory diseases. However, the high moisture in exhaled gas always brings about extra overlapping ion peaks and results in poor identification ability. In this paper, p-benzoquinone (PBQ) was introduced into IMS to eliminate the interference of overlapping ion peaks and realize the selective identification of NO. The overlapping ions caused by moisture were titrated by PBQ and then converted to hydrated PBQ anions (C6 H4 (H2 O) n ). The NO concentration could be determined by quantifying gas phase hydrated nitrite anions (N (H2 O) n ), product ions of NO. Under optimized conditions, a limit of detection (LOD) of about 1.4 ppbv and a linear range of 10–200 ppbv were obtained for NO even in 100% relative humidity (RH) purified air. Furthermore, this established method was applied to measure hourly the exhaled NO of eight healthy volunteers, and real-time monitoring the exhaled NO of an esophageal carcinoma patient during radical surgery. These results revealed the potential of the current dopant titrating IMS method in the measurement of exhaled NO for medical disease diagnosis.